Influence of input material and operational performance on the physical and chemical properties of MSW compost. (1st October 2015) - Montejo, C.; Costa, C.; Márquez, M.C.
Abstract: Certain controversy exists about the use of compost from MSW (municipal solid waste) and, specifically, from the organic fraction of MSW that has not been separated at the source. In this case, the final composition of MSW compost is related to the performance of the separation process in MBT (Mechanical and Biological Treatment) plants as well as the composition of raw materials and the particular features of composting systems. In an effort to investigate the quality of MSW compost, 30 samples of this product obtained from 10 different MBT plants were studied. The main physical and chemical properties were analyzed and were compared with the requirements of current legislation. The composting systems used to produce these compost samples were studied and the input materials were characterized. The results reveal that the heavy metal content in MSW compost was below the legal restrictions in all samples but one; however, in most of them the percentage of Pb was high. The fertilizing potential of MSW compost has been demonstrated by its high nutrient concentrations, particularly N, K, P, Ca and Mg. Nevertheless, here the percentage of inert impurities with a size larger than 2 mm, such as plastic or glass, was seen to be excessively high exceeding in some cases the legal limit. The source of such pollution lies in the composting inputs, OFMSW (organic fraction of MSW), which showed high percentages of improper materials such as plastic (9%) or glass (11%). Accordingly, the performance of the sorting stage for the collection of the raw material must be improved, as must the refining process, since this does not remove the necessary amounts of these impurities from the final compost. Highlights: The main physicochemical properties of 30 samples of MSW compost were analyzed. The technical features of the composting systems of 9 MBT plants were evaluated. The influence of the feedstock composition on the final product was proved. The concentration of heavy metals in MSW compost fulfilled legal limits. Inert materials percentage exceeds legal restrictions in some MSW composts.